Heat acclimatization does not improve VO2max or cycling performance in a cool climate in trained cyclists - Karlsen, A.; Racinais, S.; Jensen, M. V.; Nørgaard, S. J.; Bonne, T.; Nybo, L. (Scandinavian Journal of Medicine & Science in Sports, 2015)
This study investigated if well-trained cyclists improve inline image and performance in cool conditions following heat acclimatization through natural outdoor training in hot conditions. Eighteen trained male cyclists were tested for physiological adaptations, inline image, peak aerobic power output, exercise efficiency, and outdoor time trial (TT) performance (43.4 km in cool environment, ~5-13 °C) before and after 2 weeks of training in a cool (CON, n = 9) or hot (~35 °C, HA, n = 9) environment. After heat acclimatization, TT performance in the heat was improved by 16%; however, there was no change in the HA group in inline image (4.79 ± 0.21 L/min vs 4.82 ± 0.35?L/min), peak aerobic power output (417 ± 16?W vs 422 ± 17 W), and outdoor TT performance in cool conditions (300 ± 14 W/69 ± 3 min vs 302 ± 9 W/69 ± 4?min). The present study shows that 2 weeks of heat acclimatization was associated with marked improvements in TT performance in the heat. However, for the well-trained endurance athletes, this did not transfer to an improved aerobic exercise capacity or outdoor TT performance in cool conditions.